Pengaruh ukuran perusahaan, leverage, dan profitabilitas pada tax avoidance pada perusahaan konstruksi bangunan yang terdaftar di BEI periode 2014-2017 - andriessen limbong; muhammad nuryatno (Jurnal Akuntansi, 2019)
The purpose of this research is to analyze the effect of firm size, leverage, and profitability to tax avoidance. The research population was construction companies listed in Indonesia Stock Exchange (IDX) in period of 2014-2017. Sampling method used was purposive sampling method with a sample of 8 companies during the observation period of 4 years in a row for a total of 32 samples. Analysis method of this research used multiple regression. The results showed that firm size and profitabiliti has no significant effect on tax avoidance, and leverage has a significant positive effect on tax avoidance.